Knowledge and attitude towards emergency contraception in females of urban area of Lucknow, Uttar Pradesh, India - Mishra, Malvika; Tripathi, Shiv Shanker; Verma, Manish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Emergency contraception are birth control measures that, if taken after unprotected sexual intercourse, contraceptive failure, incorrect use of contraceptives or in cases of sexual assault may prevent pregnancy. The aim of the study was to assess the knowledge and attitude of female living in urban part of Lucknow district from September 2015 to August 2016. Methods: This was a descriptive, cross-sectional study conducted at RML Hospital, Lucknow from September 2015 to August 2016. A cross sectional study design was conducted and Participants were selected using simple random sampling method. Data was collected by using self-administered questionnaires. Data processing and analysis: The collected data was entered into a computer and analyzed using statistical package of social science version 20.0. Results: In this study it was found that, Out of 385 subjects 54% (209) new the correct time interval for EC to be effective and 91% (350) new that this is for prevention of unplanned pregnancy. Out of 385 subjects 77% (345) reported that they had heard the word EC from different sources, however 23% (90) reported that they never heard about that it means that still there is a scope of health awareness activities and health education to improve the knowledge of EC. Different attitudes of females towards emergency contraception some different pair of questions was asked. Out of 385 subjects 85% (329) were reported that they have positive attitudes in terms of benefits of EC to reduce the risk of unplanned pregnancy. A few number of subjects i.e. 12% (48) reported negative attitudes towards EC where as 3 % (8) did not respond. The more than half subjects i.e. 68% (260) reported that they use EC even if their partners disagreed with them where as 11% (41). Cultural belief was found as an barrier in having negative attitudes towards EC. The Religion, Occupation and educational status affect knowledge and attitudes towards EC. Conclusions: The results show that there is a scope of health awareness activities and health education to improve the knowledge and attitude towards EC.